Measurement of Resilience Communities Urban Against Unexpected (Case Study: Region 1 of Tabriz Metropolitan) - Hassan Mahmoudzadeh; mahdi herischian (تحقیقات کاربردی علوم جغرافیایی)
The occurrence of unplanned accidents is a global issue, and lack of preparedness and resilience in this area can lead to significant losses. Therefore, restitution is an important way to strengthen urban communities by utilizing their capacity. In this regard, the main objective of this research is to investigate the difference in the level of resilience indices in the three districts of a metropolitan area of ​​Tabriz. This research is in terms of the type of the target and the method is descriptive of survey type. The required data were collected using library studies and field surveys at the household level. The statistical population of the households in region 1 of Tabriz Metropolitan is estimated to be 382 families according to the Cochran formula. After data collection, the analysis of the difference in resilience with ANOVA and Tukey's post hoc test were analyzed. The results of the research show that there is a difference between the regions in terms of the resiliency indicators. So that the least amount of resilience with an average of 173/46 was allocated to households in area one and the largest with average of 252/61, to the area of ​​three regions of a metropolis of Tabriz. On the other hand, the results of the two-to-two-region comparison show that the mean of zone A alleviation in comparison with the two and three regions was 34/931 and 79/157, respectively, and the resilience of the region of two in Comparison with area 3 is 44/226 times lower than that, but the resilience of area 3 compared to the other two regions is 79/157, 44/226 times more. In the following, suggestions for improving the resilience of the study area are presented.